Application of Taguchi Method for the analysis of a multiple air jet impingement system with and without target plate motion - Barbosa, Flavia, V. (2021)
Multiple air jet impingement is a complex heat transfer process involving several parameters which interfere with the cooling and heating performance. Due to its wide applicability in engineering applications, the influence of these parameters in jet impingement efficiency has been extensively analyzed by several researchers. However, the majority of the studies developed experiments and numerical simulations to determine the effect of each parameter individually. Considering that the heat transfer performance depends on the correct combination of the multiple jet impingement parameters, the implementation of a Design of Experiments (DoE) seems to be more effective since this method allows a comparative parameter analysis as well as an optimization of the experiments and numerical simulations. In this study, a DoE based on the Taguchi method and an Analysis of Variance (ANOVA) is applied to conduct an experimental study on multiple air jets impinging a surface. This work focuses on jet-to-jet spacing (S), nozzle-to-plate distance (H), Reynolds number, and target plate geometry. Taking into consideration these four parameters, the experiments are conducted with the target plate static and in motion and the results obtained in both cases are compared. Even if the static target plate is the most studied case, the surface motion is identified in several engineering applications, such as reflow soldering and drying processes. The results show that the heat transfer of a multiple jet impingement configuration is enhanced by S=3D, H=2D for a staggered configuration, and a higher Reynolds number for both static and moving plates.